Pelatihan penulisan karya ilmiah bagi Guru SMA di Kabupaten Jeneponto - Pattaufi Pattaufi; Farida Farida (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This study aims to socialize the way to collect creditpoints through writing scientific papers as a means of teachers’career development. The result of problem identification shows that the requirements in collecting credit points for teachers in SMA Negeri 10 Bontoramba is easy for Junior Superintendent (III/a) to Administrator (IV/a), however to get promotion from Administrator (IVa) to Senior Administrator is relatively difficult. In addition, many teachers pessimistic to carry out their professional development in this case write scientific papers, thus making them reluctant and even apathetic towards their promotion. This study try to give extra coaching and counseling with several methods including lectures, questions and answers, discussions and giving assignments. The results of this coaching and counseling program shows the significant increase in motivation of teachers writing their scientific papers. It shows in their activeness in doing the assignments both individually and in groups. In addition, this scientific writing training provides benefits to teachers to develop their creativity in writing and facilitate them in the career formation of teacher ranks.